A recombinant antigen-based IgG4 ELISA for the specific and sensitive detection of Brugia malayi infection - N., Rahmah; Lim, B.H.; Anuar, A.Khairul; Shenoy, R.K.; Kumaraswami, V.; Hakim, S.Lokman; Chotechuang, P.; Kanjanopas, K.; Ramachandran, C.P. (Oxford University Press, 2001)
An IgG4 ELISA based on a novel recombinant antigen was evaluated for detection of Brugia malayi infection, using 2487 sera from various institutions: 2031 samples from Universiti Sains Malaysia, 276 blinded sera from 2 other institutions in Malaysia, 140 blinded sera from India and 40 blinded sera from Thailand. These sera were from various groups of individuals, i.e., microfilaraemics, chronic patients, endemic normals, non-endemic normals and individuals with other parasitic and bacterial infections. Based on a cut-off optical density reading of 0.300, the IgG4 ELISA demonstrated specificity rates of 95·6–100%, sensitivity rates of 96–100%, positive predictive values of 75–100% and negative predictive values of 98·9–100%. These evaluation studies demonstrated the high specificity and sensitivity of this test for the detection of active B. malayi infection. Thus, the IgG4 ELISA would be very useful as a tool in diagnosis and in elimination programmes for brugian filariasis.